2018
DOI: 10.1103/physreva.98.043856
|View full text |Cite
|
Sign up to set email alerts
|

Phase sensitivity of a Mach-Zehnder interferometer with single-intensity and difference-intensity detection

Abstract: Interferometry is a widely-used technique for precision measurements in both classical and quantum contexts. One way to increase the precision of phase measurements, for example in a Mach-Zehnder interferometer (MZI), is to use high-intensity lasers. In this paper we study the phase sensitivity of a MZI in two detection setups (difference intensity detection and single-mode intensity detection) and for three input scenarios (coherent, double coherent and coherent plus squeezed vacuum). For the coherent and dou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 45 publications
(121 reference statements)
1
78
0
Order By: Relevance
“…Since F sd = 0 for this input state, we have F = F dd . The function Υ + (α, ξ) reaches its maximum value of |α| 2 e 2r if we impose the input PMC 2θ α − θ = 0 (20) and this is the same constraint already reported and discussed in the literature for the coherent plus squeezed vacuum input [7,20,37]. In order to maximize the last term from equation (19) we have to impose the supplementary input phase-matching condition…”
Section: A Fisher Information and The Cramér-rao Boundmentioning
confidence: 67%
See 2 more Smart Citations
“…Since F sd = 0 for this input state, we have F = F dd . The function Υ + (α, ξ) reaches its maximum value of |α| 2 e 2r if we impose the input PMC 2θ α − θ = 0 (20) and this is the same constraint already reported and discussed in the literature for the coherent plus squeezed vacuum input [7,20,37]. In order to maximize the last term from equation (19) we have to impose the supplementary input phase-matching condition…”
Section: A Fisher Information and The Cramér-rao Boundmentioning
confidence: 67%
“…This is true for a wide class of input states including the single coherent, coherent plus squeezed vacuum as well as the squeezed-coherent plus squeezed vacuum states [6,7,9,31]. In references [7] and [9] it has been shown that generally ϕ opt = π/2 for a double coherent input. In this paper we will show that this is also the case for the most general input Gaussian state, namely the squeezed-coherent plus squeezed coherent input.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We discuss the double coherent input scenario [22,30], this time however with a non-balanced input beam splitter. Extending some previous results [22] for the balanced case, we find that there exists an optimum input phase mis-match different from zero for non-balanced interferometers. Moreover, we show that the maximum Fisher information stays the same, regardless of the input phase mis-match, if the transmission coefficient of the input beam splitter is carefully chosen.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting case is to replace the vacuum port with a coherent state input so that the input is a double coherent state, i.e., |α |β . The optimal phase sensitivity that can be achieved is ∆θ = 1/ |α| 2 + |β| 2 [2]. If α = β, then ∆θ = 1/ √ 2N, N being the average number of photons in any one of the inputs.…”
mentioning
confidence: 99%